Mesoporous ethanesilica materials with bimodal and trimodal pore-size distributions synthesised in the presence of cobalt ions - Neil Coville; Alufelwi Tshavhungwe (South African Journal of Science)
Mesoporous organosilica materials containing ethane groups in their framework were formed with two and three pore sizes (i.e. bimodal and trimodal pores) when synthesised by the sol-gel method in the presence of cobalt ions. The compounds 1,2-bistrimethoxysilylethane and tetraethylorthosilicate were used as silicon sources and the reactions were done in the presence of a surfactant, which served as a template. Diffuse reflectance infrared Fourier transform spectroscopy revealed that organic functional groups were incorporated into the ethanesilica. Powder X-ray diffraction and nitrogen adsorption data indicated that the mesophase and textural properties (surface area, pore volume, pore diameter) of the materials were dependent on the ageing temperature, the amount/ratio of silica precursors and cobalt ion incorporation. Secondary mesopores were drastically reduced by changing the ratio of silicon precursors.